EP008/#378 Comparative genomic analysis of ovarian clear cell carcinoma patients with and without a second primary malignancy. (4th December 2022) - Hogen, Liat; Laar, Emily Van De; Rouzbaham, Marjan; Bernardini, Marcus; Tone, Alicia; Prokopec, Stephenie; Bruce, Jeffrey; Stickle, Natalie; Pugh, Trevor
Abstract : Objectives: Previous study showed that patients with Ovarian clear cell carcinoma (OCCC) are at increased risk for developing secondary malignancy (SM). Objectives: To identify and compare germline and somatic mutations in patients with OCCC only, and patients with OCCC and a SM by whole exome sequencing (WES) analysis. To compare somatic mutations in primary and SM tissue from the same patient by WES and deep targeted sequencing. Methods: DNA was extracted from patient tumour(s) and peripheral blood samples, sequenced to identify somatic and germline mutations, copy-number variants and rearrangements in the exome. Exome sequencing was performed using the Agilent SureSelect Human All Exon (V7) panel covering 49.7 Mb across all genes annotated by RefSeq, CCDS, and GENCODE. Results: Ten patients with OCCC were selected: Five had SM and 5 patients had OCCC only. We did not uncover any pathogenic or likely-pathogenic germline variants in this cohort, as annotated by ClinVar. Consistent with previous reports in OCCC, we uncovered recurrent, oncogenic mutations in PIK3CA and loss-of-function mutations in ARID1A in 8 OCCCs. One of the two OCCCs without these mutations had somatic mutations of RRAS2 (encoding downstream target of PIK3CA pathway) and loss-of-function mutation in ARID4B, consistent with the more frequent oncogenic mechanisms in OCCC. In the SM, none of the somatic mutations were shared with the primary OCCCs. Conclusions: In this pilot study, SM did not share somatic mutation with OCCC. Larger cohort and deeper molecular analysis can be used to further understand potential common pathway contributing to development of SM in patients with OCCC.